2024
DOI: 10.1097/meg.0000000000002675
|View full text |Cite
|
Sign up to set email alerts
|

The value of whole-body dual-energy x-ray absorptiometry in assessing body composition in patients with inflammatory bowel disease: a prospective study

Anke L. Nguyen,
Madhuni Herath,
Megan Burns
et al.

Abstract: Objectives Low skeletal muscle index (SMI) is common in inflammatory bowel disease (IBD) but has an uncertain relationship with active intestinal inflammation. This study evaluated body composition by whole-body dual-energy X-ray absorptiometry (DXA) in patients with IBD and healthy controls to enable the value of formal body composition analysis to be judged. Methods Patients with IBD and sex/age-matched controls prospectively underwent full body compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They found that ultrasound was the most accurate method for measuring muscle mass compared to BIA and DXA. Furthermore, they discovered that ultrasound had the highest level of agreement with the DXA-derived muscle mass index compared to BIA [ 47 ]. Ultrasound is indeed gaining popularity in the assessment of sarcopenia.…”
Section: Diagnostic Methods To Identify Sarcopenia In Ibd Patientsmentioning
confidence: 99%
“…They found that ultrasound was the most accurate method for measuring muscle mass compared to BIA and DXA. Furthermore, they discovered that ultrasound had the highest level of agreement with the DXA-derived muscle mass index compared to BIA [ 47 ]. Ultrasound is indeed gaining popularity in the assessment of sarcopenia.…”
Section: Diagnostic Methods To Identify Sarcopenia In Ibd Patientsmentioning
confidence: 99%